2020
DOI: 10.1161/hypertensionaha.120.14916
|View full text |Cite
|
Sign up to set email alerts
|

Validation Study to Determine the Accuracy of Central Blood Pressure Measurement Using the Sphygmocor Xcel Cuff Device

Abstract: Numerous devices purport to measure central (aortic) blood pressure (BP) as distinct from conventional brachial BP. This validation study aimed to determine the accuracy of the Sphygmocor Xcel cuff device (AtCor Medical, CardieX, Sydney, Australia) for measuring central BP. 296 patients (mean age 61±12 years) undergoing coronary angiography had simultaneous measurement of invasive central BP and noninvasive cuff-derived central BP using the Xcel cuff device (total n=558 individual comparisons). A subsample (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“… 10 The most recent validation study was aimed to determine the accuracy of the SphygmoCor XCEL cuff device for measuring central blood pressure in 296 patients undergoing coronary angiography. 11 Central SBP was underestimated and with wide variability (−7.7 ± 11.0 mm Hg). In contrast to the previous study, the SphygmoCor XCEL cuff device was found not to meet the accuracy criteria for non-invasive measurement of central SBP of 5 ± 8 mm Hg.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“… 10 The most recent validation study was aimed to determine the accuracy of the SphygmoCor XCEL cuff device for measuring central blood pressure in 296 patients undergoing coronary angiography. 11 Central SBP was underestimated and with wide variability (−7.7 ± 11.0 mm Hg). In contrast to the previous study, the SphygmoCor XCEL cuff device was found not to meet the accuracy criteria for non-invasive measurement of central SBP of 5 ± 8 mm Hg.…”
Section: Discussionmentioning
confidence: 92%
“…The only appropriately powered and conducted validation studies for the XCEL device are Gotzmann et al 10 . and Schultz et al 11 . In the first study, including 502 patients, non‐invasive assessment of aortic SBP was performed by both the SphygmoCor XCEL device and the Mobil‐O‐Graph NG device and was compared with simultaneous invasive pressure measurement (through fluid‐filled catheters).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As alluded to earlier, there is a strong physiological rationale that central aortic BP may be a better predictor of cardiovascular risk than peripheral BP. However, there are myriad issues which plague the accuracy of devices that estimate central BP [31], including: (1) uncertainty on the best waveform calibration method [32]; (2) reliance on cuff BP for calibration of waveforms [33]; (3) failing to account for brachial-radial BP amplification (only applicable to radial tonometry methods) [34][35][36][37]; and (4) device-specific results due to different algorithms for the estimation of BP [31,32,38]. This final point has led to devices that estimate central BP being described as either 'type I' or 'type II' [31].…”
Section: Accuracy Of Estimated Central Aortic Blood Pressure Devicesmentioning
confidence: 99%